2019
DOI: 10.1093/ntr/ntz165
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation, Weight Gain, and the Trajectory of Estimated Risk of Coronary Heart Disease: 8-Year Follow-up From a Prospective Cohort Study

Abstract: Introduction The effect of weight gain following smoking cessation on cardiovascular risks is unclear. We aimed to prospectively investigate the association of weight gain following smoking cessation with the trajectory of estimated risks of coronary heart disease (CHD). Methods In a cohort of 18 562 Japanese male employees aged 30–64 years and initially free of cardiovascular diseases, participants were exclusively grouped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
4
10
1
1
Order By: Relevance
“…Our results are consistent with those of previous studies on the association between CVD and long-term experiences in the single domains of employment ( van Hedel et al, 2016 ), tobacco use ( Chen et al, 2019 ), and alcohol consumption ( Ortolá et al, 2019 ). Our findings also reveal that simultaneous experiences in these domains have different effects on the cardiovascular outcomes evaluated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies on the association between CVD and long-term experiences in the single domains of employment ( van Hedel et al, 2016 ), tobacco use ( Chen et al, 2019 ), and alcohol consumption ( Ortolá et al, 2019 ). Our findings also reveal that simultaneous experiences in these domains have different effects on the cardiovascular outcomes evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding studies on the health effects of long-term tobacco use patterns, one of the key findings is that people following smoking trajectories characterized by late cessation, as well as those who stop smoking earlier in life and experience weight gain afterward, are at higher risk of CVD ( Chen et al, 2019 ; Hu et al, 2018 ; Liu et al, 2020 ; Mayyas & Alzoubi, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In allo-HCT recipients, the conditioning toxicity and allo-immune response may further increase the infiltration of lymphocytes or macrophages [26][27][28][29], which eventually might result in the development of BO or IP, although the true reasons remain to be elucidated. Smoking is also associated with coronary disease and stroke [30][31][32][33]. However, the present study did not show a significant increase in these complications, since the incidence was very low even in the whole cohort.…”
Section: Discussioncontrasting
confidence: 80%
“…Similar to the abovementioned alcohol intake, the results of the present study regarding smoking should be interpreted carefully. Previous studies have shown that quitting smoking reduces the risk of cardiovascular diseases such as stroke and heart disease (Chen et al 2021;Clair et al 2013;Kim et al 2018). Although these preventive effects were attenuated for those who gain weight after smoking cessation, the beneficial effects of quitting smoking remained to exist (Chen et al 2021;Liu et al 2020).…”
Section: Smokingmentioning
confidence: 99%